2021
DOI: 10.1186/s43042-020-00125-w
|View full text |Cite
|
Sign up to set email alerts
|

Can microRNA become next-generation tools in molecular diagnostics and therapeutics? A systematic review

Abstract: Background MicroRNAs (miRNAs) represent a novel class of single-stranded RNA molecules of 18–22 nucleotides that serve as powerful tools in the regulation of gene expression. They are important regulatory molecules in several biological processes. Main body Alteration in the expression profiles of miRNAs have been found in several diseases. It is anticipated that miRNA expression profiling can become a novel diagnostic tool in the future. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 104 publications
1
10
0
1
Order By: Relevance
“…45 Neurotransmitters are category of biological messengers between cells synchronizing countless body concerning processes [52]. In present study, there is a significant decrease in Serotonin and dopamine that comes in accordance with several previous experiments revealed the negative effect of the synthetic food colorants on the hormone balance in the experimental animals [53,54] miRNA expression provides a great progression in diagnosis, monitoring as well as clarifying the underlining mechanism for numerous diseases alterations; leading to the improvement of innovative diagnostic and therapeutic prospects [55]. The intracellular process for inactivation of ROS is important for maintaining physiologic redox equilibrium by regulating the production and activity of several cellular anti-oxidative defence components, and hence plays a key role in oxidative stress development.…”
Section: Discussionsupporting
confidence: 90%
“…45 Neurotransmitters are category of biological messengers between cells synchronizing countless body concerning processes [52]. In present study, there is a significant decrease in Serotonin and dopamine that comes in accordance with several previous experiments revealed the negative effect of the synthetic food colorants on the hormone balance in the experimental animals [53,54] miRNA expression provides a great progression in diagnosis, monitoring as well as clarifying the underlining mechanism for numerous diseases alterations; leading to the improvement of innovative diagnostic and therapeutic prospects [55]. The intracellular process for inactivation of ROS is important for maintaining physiologic redox equilibrium by regulating the production and activity of several cellular anti-oxidative defence components, and hence plays a key role in oxidative stress development.…”
Section: Discussionsupporting
confidence: 90%
“…Nonetheless, a rising number of studies have indicated that subsets of miRNAs can be utilized as biomarkers in various disorders [ 76 ], and the list of miRNAs that could be employed as biomarkers is extensive [ 77 ]. In this sense, many clinical trials have been completed or are currently being conducted to test new miRNA-based diagnostic and prognostic panels [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…МиРНК-1 е една от първите микроРНКи, за която е установено, че регулира фундаментални аспекти от сърдечните функции и преди всичко процесите на кардиогенеза и патологично ремоделиране. Поради широкото ѝ разпространение в сърдечната тъкан при състояние на увреда (като остър инфаркт), експресията на тази специфична МиРНКа в кръвния серум нараства [41] На теория микроРНКите притежават много от спецификите, необходими за идеалния биомаркеррегулатори са на редица патологични процеси, широко разпространени са в биологичните течности, като кръвна плазма, слюнка, урина, цереброспинална течност и др., притежават стабилност и устойчивост [45]. Проучванията върху тях на този етап са все още в сферата на научните изследвания, вкл.…”
Section: микрорнки -нов потенциален биомаркер за сърдечна недостатъчн...unclassified